Relationship between anthropometric variables, functionality and skeletal muscle mass in physically active elderly women - Costa, Carla Eloise (2020)
Objective: to correlate the measures of calf circumference (CC) and arm circumference (AC) with skeletal muscle mass (SMM) and functionality in older adults practitioners of regular physical activities.Methods: sample was composed by 69 elderly women. The CC and AC were obtained by a tape, and height and weight were measured by digital scale. The SMM was measured by impedance bioelectrical using Janssen et al equation’s. The functionality was estimated using the Senior Fitness Test (SFT) and the 6-meter speed gait test. Descriptive analysis and Pearson Correlation test was conduted.Results: CC and AC were significantly correlated with SMM (r=0.61 and r=0.51, p<0.001, respectivetly). CC and AC were significantly correlated only with arm flexion test (r=0.31 and r=0.28, p=0.02, respectivetly).Conclusion: CC and AC showed to be good predictors of SMM in elderly women. However, these measures seems to be weak in estimating the functionality in this population.